Exploring Providers’ Perception Towards Provision of Sexual and Reproductive Health Services for Unmarried Adolescents in Gamo Zone, Southern Ethiopia: A Phenomenological Study - Sidamo NB; Gidebo KD; Wado YD; Abebe A; Meskele M (Dove Medical Press, 2021)
Nigussie Boti Sidamo,1- 3 Kassa Daka Gidebo,1 Yohannes Dibaba Wado,4 Amene Abebe,1 Mengistu Meskele1 1Department of Public Health, College of Medicine and Health Sciences, Wolaita Sodo University, Wolaita Sodo, Ethiopia; 2Department of Reproductive Health, College of Medicine and Health Sciences, Arba Minch University, Arba Minch, Ethiopia; 3Department of Public Health, PHARMA College Wolaita Sodo Campus, Wolaita Sodo, Ethiopia; 4African Populations and Health Research Center, Nairobi, KenyaCorrespondence: Nigussie Boti Sidamo; Mengistu Meskele Email Hanehalid@gmail.com; mengistu77@gmail.comBackground: Healthcare providers play a critical role in the provision of sexual and reproductive health services for adolescents. In Ethiopia, due to different reasons, including healthcare providers associated reasons, most unmarried adolescents are not accessing the services. However, little is known about healthcare providers' perception towards the provision of SRH services for unmarried adolescents. This study aimed to explore healthcare provider perception towards the provision of SRH services to unmarried adolescents in Gamo zone, Southern Ethiopia.Methods: A qualitative phenomenological research design was used in May 2021. Fifteen healthcare providers (HCPs) working in adolescent and youth sexual and reproductive health centers were involved in this study. A purposive sampling technique was used to select healthcare providers assuming they are "information-rich" regarding the phenomenon of interest. Inclusion of the study participants was continued until data saturation is reached. To analyze the data, we used inductive thematic analysis, method, and main themes, which captured the diverse views and feelings of the participants. To maintain the trustworthiness of the data, we used dependability, transferability, conformability, and credibility.Results: In this study, individual-level attributes such as healthcare provider's personal belief, attitude, and motivation; community-level influences like socio-cultural norms, religious reasons, and lack of parental support; and health system setbacks like shortage of essential medical supplies and lack of training are identified as major obstacles in the provision of sexual and reproductive health services for unmarried adolescents.Conclusion: Provision of sexual and reproductive health services for unmarried adolescents is constrained by the interplay of factors acting at an individual level, community level, and health system level. The Ministry of Health (MOH), program planners and policymakers are recommended to give due attention to fulfill the necessary inputs, improving healthcare provider's attitude and skill and engagement of religious and community leaders to create a safe and supportive environment for providing sexual and reproductive health services to unmarried adolescents.Keywords: healthcare provider, perception, sexual and reproductive health services, unmarried adolescents, Gamo Zone, Southern Ethiopia